A interação entre universidade e empresa : a perspectiva das pequenas e médias empresas brasileiras - Nunes, Jankel Dal'osto (2019)
Industries often capture information and knowledge from a variety of sources, especially customers, consumers and suppliers. There are few organizations that interact with universities to obtain information and knowledge. However, several researches point to the great potential of inter-organizational relations between University-Industry (UI), to generate important benefits for both universities, industries and society in general. When it comes to small and medium-sized enterprises (SMEs) the pursuit of knowledge through relationships with universities is even smaller. Thus, this dissertation had as main objective to analyze how the process of knowledge transfer occurs in the context of the interaction between university and SMEs in Brazil. For that, we conducted in-depth interviews, semi-structured with representatives of SMEs in the state of Rio Grande do Sul. We interviewed 13 leaders or collaborators of SMEs and 2 consultants specialists in the interaction of SMEs with the university. The research was based on the conceptual model developed by Ankrah and Al-Tabbaa (2015), which presents four main dimensions of the University-Industry Interaction (UII) process: motivators, interaction activities, intervening factors (barriers and/or facilitators), and interaction results. Thus, in the present dissertation, these factors were identified, categorized and analyzed according to the vision of Brazilian SMEs. Among the main theoretical contributions of the study are the redesign of the UI interaction process through the identification of variables in the context of Brazilian SMEs. In addition, this study presented several new factors, that is, antecedent, intervenient and consequent of UII that had not yet been identified in the theory. Regarding the managerial contributions, this study presented to the leaders of SMEs, how universities can help their companies, and what positive results the interactions with universities can generate for SMEs. For university leaders, this study presents the main barriers attributed to universities in the view of SMEs, that is, points that universities need to improve in order for the interaction to succeed. In addition, the study presented the factors that motivate SMEs to look for universities, allowing universities to invest in these motivators to attract SMEs.